A study on the effect of university education service quality on trust and positive behavioral intentions: Focusing on students in technical universities in Jiāngsū Shěng - Wei, Chen; Hao, Jin Zi; Seung-Wan, Ju (Edelweiss Applied Science and Technology, 2025)
The purpose of this study was to link the quality of university education services perceived by university students in China with trust and to suggest a way to inspire positive behavioral intentions among university students in China. In order to achieve the purpose of the study, based on domestic and foreign literature and previous studies, the theoretical basis regarding university students in China, university education service quality, trust, and positive behavioral intentions was prepared. Based on this, a research model and research hypothesis were set up and verified through empirical analysis. The results of the empirical analysis are as follows: The educational content, educational environment, and teaching ability of the university education service quality were found to have a significant positive effect on trust, so Hypotheses 1, 2, and 3 were accepted. In addition, Hypothesis 4 was also accepted because it was found that trust had a significant positive effect on positive behavioral intention. The implications of the empirical analysis of this study are as follows: First, in order for universities in China to attract students, they should not have a tendency to be biased towards certain factors of university education service quality, and continuous efforts should be made to build trust through various factors of university education service quality. Second, to raise the trust of students, universities should actively seek ways to inspire the trust of students in various aspects by developing programs that can enhance the quality of educational services, such as improving the educational environment, teaching skills, and educational content. Third, enhancing trust in the university through the quality of educational services provided to current students can generate behavioral intentions among them. Therefore, the university should develop strategies to consistently maintain the reliability of its educational service quality.